Uptake of Arsenic by Irrigated Vegetables and Cooked Food Products in Burkina Faso - Clair-Caliot, Guillaume; Marks, Sara J.; Hug, Stephan J.; Bretzler, Anja; N'guessan, N'goran Djo; Tihe, Sussue Franck Kevin; Lalanne, Franck (Frontiers in Water, 2021)
As compared to the Asian lowlands, environmental exposure to arsenic (As) in West Africa has received little attention. Recent studies have found As contamination of groundwater in Burkina Faso. As-contaminated groundwater is used for drinking and increasingly also for irrigation of staple foods. This study assesses the extent to which irrigation and cooking of staple foods in Burkina Faso influence plant uptake and dietary consumption of As, respectively. Using a greenhouse experimental set up, we evaluated the transfer of As from irrigation water with 0, 100, 500 and 1000 µg/L As(V) to the organs and edible parts of seven commonly consumed vegetables (amaranth, carrot, green bean, lettuce, okra, spinach, and tomato). Next, we cooked the greenhouse-cultivated vegetables as well as externally purchased foods with As-free and As-spiked waters. The As content in all plant organs increased with increasing As in the irrigation water. At the mid-point (500 µg/L) spike level, As concentrations in the edible parts (from highest to lowest) were: spinach (6.6 ± 0.5 μg/g); lettuce (3.9 ± 0.1 μg/g); carrot (3.5 ± <0.1 μg/g); amaranth (2.2 ± <0.1μg/g); okra (0.9 ± <0.1 μg/g); green bean (0.8 ± <0.1 μg/g); and tomato (0.2 ± <0.1 μg/g). The edible parts of leafy vegetables irrigated with As-spiked water had higher average As content (4.9 ± 4.5 µg/g) than taproot (2.9 ± 2.0 µg/g) and non-leafy vegetables (0.8 ± 1.1 µg/g). Cooking with an excess volume of As-free water reduced the arsenic content in the cooked vegetables by 39% on average, while cooking with As contaminated water transferred arsenic to the cooked food. The As content in steamed foods was 8 to 18 times lower than in boiled foods. Based on human health risk estimates, we recommend to plant leafy vegetables in areas with low As concentrations in irrigation water and we propose the maximum As concentrations of 100 µg/L for the cultivation of carrot, 500 µg/L for green bean, spinach and lettuce and 1000 µg/L for amaranth. In As-contaminated areas, mitigation strategies include the cultivation of non-leafy vegetables such as tomato and okra and steaming the food instead of boiling.